Avaliação da atividade antimicrobiana de hipoclorito de sódio (NaClO) em Salmonella enterica isolada de peixe nativo (tambaqui – Colossoma macropomum) - Nunes, Nathaly Barros (2023)
The practice of aquaculture over the years has produced tons of native fish all over the world. Fish is a nutritionally rich product, however, easily contaminated by deteriorating and pathogenic microorganisms, such as Salmonella spp. This pathogen is not part of the natural microbiota of fish, which become intermediate hosts through contamination, and may cause foodborne infection in humans who consume it. Control Salmonella spp. in fish processing is essential for the advancement of trade and development of the production chain. In this context, this study aimed to identify the best concentration of sodium hypochlorite (NaClO, exposure time and water temperature, which allows the best possible antimicrobial effect on the population of Salmonella spp. For this purpose, the level of inactivation of Salmonella was evaluated Enteritidis ATCC 13076 and Salmonella Schwarzengrund challenged at different times ranging from 5 minutes to 38 and a half minutes, temperatures between 5°C to 38.5°C and NaClO concentrations between 0.36 ppm to 6.36 ppm through an experiment with rotational central composite design (DCCR). The results found confirm that the concentration of 5 ppm, recommended by the regulatory bodies in Brazil, was efficient for the inactivation of Salmonella Enteritidis, where this effect was achieved regardless of the other variables used. However, it could be verified that the concentration of 6.36 ppm generated a reduction of 7 log10 CFU/ml. For the strain of Salmonella Schwarzengrund it was observed that the conception NaClO concentration and exposure time acted significantly in inactivation, not suffering influence from the temperature variable. Thus, the analyzes carried out indicate that strains of Salmonella spp. used in an in vitro experiment were sensitive to concentrations equal to or greater than that recommended by legislation, with the need for effective methods, such as longer exposure time combined with the recommended NaClO concentration to be adopted in industries to promote a better control point to guarantee a food safe for the consumer population.